Pseudo-Consent in Indonesian Digital Commerce: Reframing Hurriyah at-Ta'aqud through Maqasid Systems Analysis - Hasan, Jamaludin; Sarib, Suprijati; Jan, Radlyah Hasan; Harun, Nurlaila (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
Indonesian e-commerce and fintech increasingly rely on clickwrap terms that convert consent into a procedural “I Agree”, creating pseudo-consent and widening power and information asymmetries. This article reframes hurriyah at-ta'aqud (freedom of contract) by testing whether digital assent satisfies ridha, bayan (clarity), and ikhtiyar (voluntariness) in a plural, multicultural marketplace. Using juridical-normative research and document analysis of standard clauses from Shopee, Tokopedia, and GoPay, the study applies Jasser Auda’s Maqasid Shariah systems approach (cognition, wholeness, openness) to evaluate substantive validity beyond formal compliance. Findings show recurring exoneration clauses that shift system, data, and delivery risks to users, embedding jahalah and gharar and conflicting with la darar (no-harm) and hifz al-mal (protection of wealth). The paper proposes a two-layer validity model procedural legality and maqasid-based fairness supported by indicators for invalidating harmful clauses and redesigning notice-and-choice interfaces. It recommends integrating amanah and shiddiq as enforceable governance standards, strengthening consumer remedies and regulatory oversight in Indonesia’s digital commerce.